Interview with Salahuddin Ahmed on the trade union movement and M.N. Roy. Interviewed in Dhaka, 21/04/2000 - Kabir, Shahriar.
Interview with Salahuddin Ahmed on the trade union movement and M.N. Roy. Interviewed in Dhaka, 21/04/2000.